Problem Aplikasi Paham Gender dalam Keluarga - Saiful Anwar (Universitas Darussalam Gontor, 2015)
In the Western world Gender accused as family destroyer movement. This Feminists ideology encourages the women to leave the family, in fact looking at the family as an institution of oppression against women. However in Indonesia, Gender serve family empowerment program that Gender Perspective Family Education. Gender Perspective Family Education is a government program that is based on Presidential Instruction Number. 9 of 2000 on gender mainstreaming. As awareness effort of understanding the rights and obligations of male roles and women. The program is integrated through life skills education for justice and gender equality in the family. Yet the program adopted from foreign concept turned out to have some confusion. First, the using of word gender plagiarized from some Western leaders was necessary to attempt to equalize men and women in all fields. Second, the gender equality as a goal of Gender Perspective Family Education is contrary to the reality of human life, biologically and religion. Third, the concept of natural and unnatural taught by this program seeks to abolish the nature of women as mothers. Fourth, the program negates religious element in the learning process, whereas the families in Indonesia can not be separated from religious element. Thus it was very clear that Gender Perspective Family Education is not a step empowering the families but the step endanger the family.